Neogene volcanism in Elazig-Tunceli area (eastern Anatolia): geochronological and petrological constraints - Agostini, Samuele; Savascin, Mehmet Yilmaz; Di Giuseppe, Paolo; Di Stefano, Flavio; Karaoglu, Ozgur; Lustrino, Michele; Onal, Ayten Oztufekci (Soc Geologica Italiana, 2019)
The Elazig and Tunceli provinces in eastern Anatolia host a complex succession of Miocene-Pleistocene effusive and explosive volcanic rocks, divided into four distinct volcanic phases. The most abundant and widespread products are the calcalkaline Mazgirt volcanic rocks, characterized by wide Sr isotope variations ( Sr-87/Sr-86 similar to 0.7054-0.7077) and narrower Nd-143/Nd-144 (similar to 0.51246-0.51260) and Pb isotopes (e.g., Pb-206/Pb-204 similar to 18.89-19.13). New 40Ar-39Ar ages indicate that Mazgirt volcanic activity occurred between similar to 16.3 and 15.1 Ma. The other three volcanic phases are represented by the Tunceli mildly alkaline basaltic lavas (similar to 11.4-11.0 Ma), the Pliocene Karakocan (similar to 4.1 Ma) and Pleistocene Elazig (similar to 1.9-1.6 Ma) Na-alkali basaltic lavas with clear OIB-like geochemical signature. Mazgirt volcanics can be subdivided on the base of mode of emplacement into lava flows and lava domes units characterized by petrographic, chemical and isotopic differences: lava flows are calcalkaline, whereas lava domes mostly belong to a high-K calcalkaline series and are, on average, more LREE- and Sr-87-enriched. Lava domes are more porphyritic, with a phenocryst assemblage dominated by amphibole, whereas plagioclase and clinopyroxene are the most abundant phenocryst phases in lava flows, pointing out that evolution of dome magmas occurred in conditions of slightly higher pressure, favouring the crystallization of hydrous phases. The Karabakir Formation, previously reported as late MiocenePliocene, encloses Mazgirt volcanics and is capped by Tunceli basalts. These new age data constrain the Karabakir Formation emplacement from early to late Miocene. The evolution of this igneous activity mirrors the geodynamic framework of the region: the early-middle Miocene Mazgirt volcanics represent arc volcanism related to Eurasia-Arabia convergence. The late Miocene Tunceli basalts postdate the onset of post-collisional tectonics in Eastern Anatolia, whereas the Karakocan and Elazig volcanic rocks were emplaced after the initiation of strike-slip motion on the North Anatolian and East Anatolian Fault systems. The Elazig and Tunceli provinces in eastern Anatolia host a complex succession of Miocene-Pleistocene effusive and explosive volcanic rocks, divided into four distinct volcanic phases. The most abundant and widespread products are the calcalkaline Mazgirt volcanic rocks, characterized by wide Sr isotope variations ( Sr-87/Sr-86 similar to 0.7054-0.7077) and narrower Nd-143/Nd-144 (similar to 0.51246-0.51260) and Pb isotopes (e.g., Pb-206/Pb-204 similar to 18.89-19.13). New 40Ar-39Ar ages indicate that Mazgirt volcanic activity occurred between similar to 16.3 and 15.1 Ma. The other three volcanic phases are represented by the Tunceli mildly alkaline basaltic lavas (similar to 11.4-11.0 Ma), the Pliocene Karakocan (similar to 4.1 Ma) and Pleistocene Elazig (similar to 1.9-1.6 Ma) Na-alkali basaltic lavas with clear OIB-like geochemical signature. Mazgirt volcanics can be subdivided on the base of mode of emplacement into lava flows and lava domes units characterized by petrographic, chemical and isotopic differences: lava flows are calcalkaline, whereas lava domes mostly belong to a high-K calcalkaline series and are, on average, more LREE- and Sr-87-enriched. Lava domes are more porphyritic, with a phenocryst assemblage dominated by amphibole, whereas plagioclase and clinopyroxene are the most abundant phenocryst phases in lava flows, pointing out that evolution of dome magmas occurred in conditions of slightly higher pressure, favouring the crystallization of hydrous phases. The Karabakir Formation, previously reported as late MiocenePliocene, encloses Mazgirt volcanics and is capped by Tunceli basalts. These new age data constrain the Karabakir Formation emplacement from early to late Miocene. The evolution of this igneous activity mirrors the geodynamic framework of the region: the early-middle Miocene Mazgirt volcanics represent arc volcanism related to Eurasia-Arabia convergence. The late Miocene Tunceli basalts postdate the onset of post-collisional tectonics in Eastern Anatolia, whereas the Karakocan and Elazig volcanic rocks were emplaced after the initiation of strike-slip motion on the North Anatolian and East Anatolian Fault systems. The Elazig and Tunceli provinces in eastern Anatolia host a complex succession of Miocene-Pleistocene effusive and explosive volcanic rocks, divided into four distinct volcanic phases. The most abundant and widespread products are the calcalkaline Mazgirt volcanic rocks, characterized by wide Sr isotope variations ( Sr-87/Sr-86 similar to 0.7054-0.7077) and narrower Nd-143/Nd-144 (similar to 0.51246-0.51260) and Pb isotopes (e.g., Pb-206/Pb-204 similar to 18.89-19.13). New 40Ar-39Ar ages indicate that Mazgirt volcanic activity occurred between similar to 16.3 and 15.1 Ma. The other three volcanic phases are represented by the Tunceli mildly alkaline basaltic lavas (similar to 11.4-11.0 Ma), the Pliocene Karakocan (similar to 4.1 Ma) and Pleistocene Elazig (similar to 1.9-1.6 Ma) Na-alkali basaltic lavas with clear OIB-like geochemical signature. Mazgirt volcanics can be subdivided on the base of mode of emplacement into lava flows and lava domes units characterized by petrographic, chemical and isotopic differences: lava flows are calcalkaline, whereas lava domes mostly belong to a high-K calcalkaline series and are, on average, more LREE- and Sr-87-enriched. Lava domes are more porphyritic, with a phenocryst assemblage dominated by amphibole, whereas plagioclase and clinopyroxene are the most abundant phenocryst phases in lava flows, pointing out that evolution of dome magmas occurred in conditions of slightly higher pressure, favouring the crystallization of hydrous phases. The Karabakir Formation, previously reported as late MiocenePliocene, encloses Mazgirt volcanics and is capped by Tunceli basalts. These new age data constrain the Karabakir Formation emplacement from early to late Miocene. The evolution of this igneous activity mirrors the geodynamic framework of the region: the early-middle Miocene Mazgirt volcanics represent arc volcanism related to Eurasia-Arabia convergence. The late Miocene Tunceli basalts postdate the onset of post-collisional tectonics in Eastern Anatolia, whereas the Karakocan and Elazig volcanic rocks were emplaced after the initiation of strike-slip motion on the North Anatolian and East Anatolian Fault systems. The Elazig and Tunceli provinces in eastern Anatolia host a complex succession of Miocene-Pleistocene effusive and explosive volcanic rocks, divided into four distinct volcanic phases. The most abundant and widespread products are the calcalkaline Mazgirt volcanic rocks, characterized by wide Sr isotope variations ( Sr-87/Sr-86 similar to 0.7054-0.7077) and narrower Nd-143/Nd-144 (similar to 0.51246-0.51260) and Pb isotopes (e.g., Pb-206/Pb-204 similar to 18.89-19.13). New 40Ar-39Ar ages indicate that Mazgirt volcanic activity occurred between similar to 16.3 and 15.1 Ma. The other three volcanic phases are represented by the Tunceli mildly alkaline basaltic lavas (similar to 11.4-11.0 Ma), the Pliocene Karakocan (similar to 4.1 Ma) and Pleistocene Elazig (similar to 1.9-1.6 Ma) Na-alkali basaltic lavas with clear OIB-like geochemical signature. Mazgirt volcanics can be subdivided on the base of mode of emplacement into lava flows and lava domes units characterized by petrographic, chemical and isotopic differences: lava flows are calcalkaline, whereas lava domes mostly belong to a high-K calcalkaline series and are, on average, more LREE- and Sr-87-enriched. Lava domes are more porphyritic, with a phenocryst assemblage dominated by amphibole, whereas plagioclase and clinopyroxene are the most abundant phenocryst phases in lava flows, pointing out that evolution of dome magmas occurred in conditions of slightly higher pressure, favouring the crystallization of hydrous phases. The Karabakir Formation, previously reported as late MiocenePliocene, encloses Mazgirt volcanics and is capped by Tunceli basalts. These new age data constrain the Karabakir Formation emplacement from early to late Miocene. The evolution of this igneous activity mirrors the geodynamic framework of the region: the early-middle Miocene Mazgirt volcanics represent arc volcanism related to Eurasia-Arabia convergence. The late Miocene Tunceli basalts postdate the onset of post-collisional tectonics in Eastern Anatolia, whereas the Karakocan and Elazig volcanic rocks were emplaced after the initiation of strike-slip motion on the North Anatolian and East Anatolian Fault systems.
Keywords: Neogene volcanism; Eastern Anatolia; Ar-Ar geochronology; radiogenic isotopes; petrology